Cardiovascular and cerebrovascular responses to urodynamics testing after spinal cord injury: The influence of autonomic injury - Sahota, Inderjeet S.; Lucci, Vera-Ellen M.; McGrath, Maureen S.; Ravensbergen, H. J. C. (Rianne); Claydon, Victoria E. (Frontiers in Physiology, 2022)
Autonomic dysfunction is a prominent concern following spinal cord injury (SCI). In particular, autonomic dysreflexia (AD; paroxysmal hypertension and concurrent bradycardia in response to sensory stimuli below the level of injury) is common in autonomically-complete injuries at or above T6. AD is currently defined as a >20mmHg increase in systolic arterial pressure (SAP) from baseline, without heart rate (HR) criteria. Urodynamics testing (UDS) is performed routinely after SCI to monitor urological sequelae, often provoking AD. We, therefore, aimed to assess the cardiovascular and cerebrovascular responses to UDS and their association with autonomic injury in individuals with chronic (>1 year) SCI. Following blood draw (plasma norepinephrine [NE]), continuous SAP, HR, and cerebral blood flow velocity (MCAv) were recorded at baseline (10-minute supine), during standard clinical UDS, and recovery (10-minute supine) (n=22, age 41.1±2 years, 15 male). Low frequency variability in systolic arterial pressure (LFSAP; a marker of sympathetic modulation of blood pressure) and cerebral resistance were determined. High-level injury (≥T6) with blunted/absent LFSAP (<1.0mmHg2) and/or low plasma NE (<0.56nmol•L-1) indicated autonomically-complete injury. Known electrocardiographic markers of atrial (p-wave duration variability) and ventricular arrhythmia (T-peak–T-end variability) were evaluated at baseline and during UDS. Nine participants were determined as autonomically-complete, yet 20 participants had increased SAP >20mmHg during UDS. Qualitative autonomic assessment did not discriminate autonomic injury. Maximum SAP was higher in autonomically-complete injuries (207.1±2.3 mmHg) than autonomically-incomplete injuries (165.9±5.3 mmHg) during UDS (p<0.001). HR during UDS was reduced compared to baseline (p=0.056) and recovery (p=0.048) only in autonomically-complete lesions. MCAv was not different between groups or phases (all p>0.05). Cerebrovascular resistance index was increased during UDS in autonomically-complete injuries compared to baseline (p<0.001) and recovery (p<0.001). Risk for both atrial and ventricular arrhythmia increased during UDS compared to baseline (p<0.05), particularly in autonomically-complete injuries (p<0.05). UDS is recommended yearly in chronic SCI but is associated with profound AD and an increased risk of arrhythmia, highlighting the need for continued monitoring during UDS. Our data also highlight the need for HR criteria in the definition of AD and the need for quantitative consideration of autonomic function after SCI.